Penyuluhan Gerakan Gemar Menabung Sejak Dini di KB Muslimat NU 05 Rudhotul Huda: Counseling on the Early Saving Movement at KB Muslimat NU 05 Rudhotul Huda - Siska Anggie Melani Siska; Lisa Nur Khasanah Lisa; Olifia Nur Afifa Olifia; Hendri Hermawan Adinugraha Hendri (CONSEN: Indonesian Journal of Community Services and Engagement, 2022)
Saving is actually instilled in children from an early age, both by parents (family), teachers (schools) and by financial institutions such as banks. A person who is able to make decisions in managing his finances will not experience difficulties in the future and shows healthy behavior so that he is able to determine the priority scale about what his needs and desires are. The purpose of the research at KB Muslimat NU 05 Rudhotul Huda is that introduction from childhood will help children get used to managing their money properly and correctly from childhood to adulthood and be able to make the right decisions in using their money. Based on the results of research that the level of knowledge of children about money, savings and how to manage money is also still very low.